Direct spatial development tools at the local level vs. the economic development as a research problem - Nowak, Maciej J. (Journal of Public Governance, 2013)
Th e purpose of this paper is to determine, on the basis of case studies, the economic consequences of the application by the local municipal authorities of spatial development plans and of documents concerning the conditions for construction and land management. In particular, the author attempts to verify whether the space management concept adopted in various municipalities had an impact on their economic development, especially the number of businesses in the area. For each municipality, the author describes the number of location decisions per one thousand inhabitants; the number of documents concerning the conditions for construction and land management which were rejected; as well as the number of local plans in the municipalities that encourage the development of entrepreneurship at a local scale.